Canva-Based Digital Teaching Materials for Elementary Literacy: A Feasibility and Practicality Study - Indah Catur Riyanti; Taufiqulloh Taufiqulloh; Khusnul Khotimah (Universitas Pendidikan Mandalika, 2026)
This study aims to examine the feasibility and practicality of Canva-based digital teaching materials for enhancing elementary school students’ literacy skills. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. The participants consisted of fourth-grade students and teachers from two elementary schools in Taman District, Pemalang Regency. Data were collected through observations, literacy tests (pre-test and post-test), questionnaires, interviews, and documentation. Feasibility data were obtained through expert validation involving material and media experts, while practicality data were gathered from teachers’ and students’ responses during a limited trial. Quantitative data were analyzed using descriptive statistics and N-Gain analysis, whereas qualitative data were analyzed using Miles and Huberman’s interactive model. The results indicate that the Canva-based digital teaching materials are valid based on expert judgment, with an average feasibility score of 4.36, and practical based on user responses, with an average practicality score of 4.34. Furthermore, students’ literacy skills showed improvement after using the developed materials, as reflected by an N-Gain value of 0.55, which falls within the moderate category. These findings suggest that Canva-based digital teaching materials are feasible and practical for supporting literacy learning in elementary schools.